ANALISIS SEKTOR POTENSIAL KABUPATEN MUARO JAMBI DENGAN METODE LOCATION QUOTIENT - N Nurvaizah; Ahmad Syukron Prasaja (Pusat Riset dan Publikasi, 2023)
Regional Development Is increasingly complex in the current era of regional autonomy, resulting in increasingly fierce competition between regions.in order for people’s welfare to remain stable and even increase, local governments must increase the competitiveness of their regions. In order for regional development to be more focused, one of the efforts that can be made is to detect te potencial sectors of the area. Therefore, this study aims to determine the potential sectors in muaro jambi regency so that local goverments can focus on developing their regions. The location quetiont (LQ) Approach is used in analzying the potential sectors of Muaro Jambi Regency. So that it can be concluded, the potential sectors of Muaro Jambi Regency Are the Construction sector, the agriculture, forestry and fishery sectors, transportation and werehousing, the corporate service sector.